Strategic Consensus on the Value of Immuno-Oncology in Portugal - . . (Formifarma, LDA., 2016)
The Institute of Health Sciences of Universidade Católica Portuguesa held on September 27th a public session to present the results of ADVANCE IO - Strategic Consensus on the Value of Immuno-Oncology in Portugal. The study, an initiative of the Institute of Public Health of the Universidade Católica Portuguesa, is the result of the application of the Consensus Method to the work of a Think Tank that brought together about 30 key players in the different dimensions of the disease, including scientists from the immunotherapy, public health and management areas, representatives of patient organizations, medical experts in medical oncology and pulmonology, deputies and representatives of political parties represented in the Parliament, services of the Ministry of Health, the three most relevant professional orders to the subject (medical, pharmacist and nurse) and the national association representing the pharmaceutical industry. This initiative aims to seek answers to the new challenges that immunotherapy presents, in particular with regard to providing the best possible care to patients through research of the system efficiencies and considering the scarce resources available. In this section, we publish a brief summary of the document, and also present the set of considerations that share a high level of agreement among the participants, along with the main conclusions of the study. The document is available at: http://avanco.io/avanco-io/.